2021
DOI: 10.1111/psyp.13874
|View full text |Cite
|
Sign up to set email alerts
|

EEG‐neurofeedback and executive function enhancement in healthy adults: A systematic review

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 86 publications
(197 reference statements)
0
29
0
Order By: Relevance
“…Considering the scores in Cz and Fz, the neurofeedback needed to include these sites. Furthermore, neurofeedback on frontal-midline theta (Fz) has been shown to be frequently more effective than neurofeedback protocols that do not include Fz [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the scores in Cz and Fz, the neurofeedback needed to include these sites. Furthermore, neurofeedback on frontal-midline theta (Fz) has been shown to be frequently more effective than neurofeedback protocols that do not include Fz [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The use of neurofeedback in interventions for ADHD began in 1973, although the first study with positive results was published in 1976 [ 17 ]. Since then, various studies have reported benefits from using neurofeedback in infants, with improvements in behavior, attention, and impulsivity control (e.g., [ 18 , 19 , 20 , 21 , 22 ]). A meta-analysis by Arns et al [ 14 ] concluded that treatment of ADHD with neurofeedback could be considered “effective and specific”, with a large effect size for attention deficit and impulsivity and a moderate effect size for hyperactivity.…”
Section: Introductionmentioning
confidence: 99%
“…SMR-NFb training is a brainwave technique whose main effects on neural processes have been associated with the attenuation of somatosensory information flux to the cortex during SMR activity [ 3 , 8 , 9 , 11 ], which can persist in the form of cognitive and behavioral improvements after the training session [ 54 ]. The underlying mechanisms supporting a persistent effect are still poorly described to date regarding a single NFb session.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence regarding the positive effects on cognitive performance of NFB training is gradually emerging (Enriquez-Geppert et al, 2017). Recent studies testing NFB as a neurorehabilitation technique highlighted its efficacy on performance enhancement of several cognitive functions such as executive functions (Viviani & Vallesi, 2021), attention and memory (Yeh et al, 2020) in healthy individuals. Similarly, NFB seems to be effective in improving quality of life and as a nonpharmacological treatment for the relief of cognitive symptoms of many clinical conditions such as mild cognitive impairment (Trambaiolli et al, 2021), poststroke (Renton et al, 2017), and traumatic brain injury (Ali et al, 2020).…”
Section: Figure 2 Scatter Plot Between Days Of Treatment and Collected Variablesmentioning
confidence: 99%